Effect of Age, Gender, Side and Impaction Types on Surgical Difficulty During Mandibular Third Molar Extraction. - Bhuju, Krishna Gopal; Shrestha, Sujita; Karki, Riwaj; Aryal, Sameer (Medical Journal of Shree Birendra Hospital, 2018)
Aim: To study the effect of age, gender, side and impaction types on surgical difficulty during mandibular third molar extraction through the data collected over a period of one year by single maxillofacial surgeon. All the extractions were performed under the same environment and conditions. Methods: Descriptive clinical study of 401 patients was carried out between the ages of 16 to 45years. Age, gender, impaction side and impaction types (according to the winter classification) were recorded on proforma. Duration of surgery for each patient was recorded after starting incision to the completion of suture which was divided into less than 10 minutes (mild), 11 to 20 minutes (moderate) and above 21 minutes (severe). Pearson’s Chi-square test was used for data analysis and significance level was less than or equal to 0.05. Results: Among 401 participants, 225 (56.1%) were male and 176 (43.9%) were female. Mean age was 31.5 years and mean operation time was 17.59 minutes. After statistical analysis there was a significant correlation among gender and side of impaction where p value is 0.043 0.048 respectively. Conclusion: There is a statistically significant correlation between gender and side of impaction with duration of surgery which is considered as the objective measure of surgical difficulty whereas age and impaction types didn’t show any significant correlation.